A Study of Geologists in India : 1955 Manpower Studies-II Geo: July : 1958 - Planning Commission (Planning Commission, 1968)
The 1955 report on geologists in India provides a detailed assessment of the size, composition, and employment conditions of the geological workforce. Drawing on data from the National Register and academic records, it highlights a predominantly young workforce, moderate registration coverage, limited doctoral-level specialization, and varied employment across government, education, industry, and research. The study underscores the importance of maintaining accurate manpower data and strengthening training and specialization to meet India’s growing needs in geological exploration and resource development.
Planning Commission Perspective Planning Division
Planning Commission Perspective Planning Division
Keywords: Geologist Manpower In India; National Register Of Geologists; Geological Workforce Analysis; Planning Commission Of India; Scientific And Technical Manpower; Employment Patterns; Geological Specialization; Salary Structure; Resource Development; Human Resource Planning